Lactose-Astaxanthin Increased the Frozen Semen Quality of Gembrong Goat in Conservation Efforts (LAKTOSA-ASTAXANTHIN MENINGKATKAN KUALITAS SEMEN KAMBING GEMBRON DALAM UPAYA KONSERVASI) - Bebas, Wayan; Gorda, Wayan; Trilaksana, I Gusti Ngurah Bagus; Laksmi, Desak Nyoman Dewi Indira; Pemayun, Tjok Gede Oka (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
This research was conducted to produce a formula of diluent for the manufacture of frozen semen of Gembrong goat. Yolk phosphate was used as a basic diluent with the addition of anti-cold shock, antioxidants and combination of anti-cold shock-antioxidant. The research design used a completely randomized design with three kinds of treatments; T1: the addition of lactose 0.6% (anti-cold shock), T2: the addition of astaxanthin 0.004% (antioxidant), and T3: a combination of 0.6% lactose-Astaxanthin 0.004% (combination of anti-cold shock and antioxidants). The addition of DMSO 6% was used in each treatment as intracellular cryo protectants. The freezing process was done with the gradual freezing with conventional techniques. Examination of the quality of semen by thawing prior included progressive motility, viability, and abnormalities. The results showed that anticoldshock-antioxidant combination (0.6% lactose -Astaxanthin 0.004%) produced the best semen quality with progressive motility, viability, and less abnormalities as follow 44.00 + 3.46%, 59.00 + 1.85%, and 14.00 + 0.76% respectively. It was concluded that the addition of a combination of 0.6% lactose-Astaxanthin 0.004% on the phosphate yolk diluent with 6% DMSO as  intracellular   produced best quality of frozen  goat Gembrong semen that suitable for use in artificial insemination and in vitro fertilization.